The anti-Jacobin novel : British conservatism and the French Revolution - Grenby, M. O. (Matthew Orville), 1970- (Cambridge studies in Romanticism, 2001)
M.O. Grenby's book offers an insight into the society which produced and consumed anti-Jacobin novels. He examines the strategies used by conservatives in their fiction, thus shedding new light on how the anti-Jacobin campaign was understood and organised in Britain.